Discover Tai Chi for balance & mobility [videorecording (DVD)]. - Cole, Scott, 1962- (BayView Fitness, 2010)
Discover improved balance, strength, flexibility, and mobility at any age with gentle therapeutic Tai Chi-inspired exercise from America's premier Tai Chi and fitness expert, Scott Cole. Guiding you through a delectable continuum of breath, movement, Tai Chi, Chi Kung, stretching, and chair exercise, Discover Tai Chi for Balance and Mobility delivers easy-to-follow, effective exercises to help prevent falling, while improving overall balance, strength, flexibility, and mobility.